Implementation of the Project-based Learning Concept in terms of the Independent Curriculum in Developing Learning Creativity in Islamic Religiouas Education - Nasri Indra Padang; Firdaus W Suhaeb (JPASDEV : Journal of Public Administration and Sociology of Development, 2023)
Indonesia's future can be seen from the school's efforts to form, design and manage a system that is in accordance with the increasingly rapid developments of the era. In dealing with these problems, it is necessary for educational institutions to participate in adjusting to these conditions by finding appropriate learning model solutions. A system-independent curriculum that is designed and is still being hotly discussed to become the newest education system combined with Project-Based Learning solutions that have projects that accompany the learning process. This study aims to describe the implementation of Project-Based Learning at SMA Muhammadiyah 4 Surabaya in terms of the independent curriculum and to describe students' creativity in learning Islam through Project-Based Learning. The research method used is a qualitative method with a case study approach. As for the research results obtained, namely the learning model that has been applied has been successful and in accordance with the abilities and expectations of creativity and the independent curriculum because students can accept the application of Project-Based Learning as a learning model that encourages them to increase their creativity in learning according to the independent curriculum. There are recommendations for other researchers, that there are still many solutions to facilitate the learning process. This does not mean that Project-Based Learning is the only solution, but there are many other alternative ways that are even suitable to be applied to develop students' creativity. Recommendations for educators, it is hoped that they can prepare learning models for this learning model in a more well-conceived concept so that students can achieve more optimally.Keywords:Project based Learning, Independent Curriculum, Student Creativity, Islamic Religious Education